2022
DOI: 10.1177/13634607221085485
|View full text |Cite
|
Sign up to set email alerts
|

“I Didn’t Know Ace Was a Thing”: Bisexuality and pansexuality as identity pathways in asexual identity formation

Abstract: Identity formation for asexual people can be complicated by limited societal awareness of asexualities. Consequently, people who eventually identify on the asexuality spectrum often adopt other sexual identities in their early lives. In this paper, we extend sexual identity development theory by analyzing the identity trajectories of asexual-spectrum people who once identified as bisexual or pansexual. Quantitative data suggests that about half of asexual-spectrum respondents once identified as bisexual or pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Taken together with the results of belonging to Canada, it appears that asexuals and bisexuals have somewhat worse outcomes than other SGMs. The lower visibility and social profile of asexuals and bisexuals might be behind these results (Berbary & Guzman, 2018; Robinson, 2014; Winer et al, 2022). Further research, preferably qualitative, is warranted to verify the accuracy of this conjecture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together with the results of belonging to Canada, it appears that asexuals and bisexuals have somewhat worse outcomes than other SGMs. The lower visibility and social profile of asexuals and bisexuals might be behind these results (Berbary & Guzman, 2018; Robinson, 2014; Winer et al, 2022). Further research, preferably qualitative, is warranted to verify the accuracy of this conjecture.…”
Section: Resultsmentioning
confidence: 99%
“…Still, in a community as diverse as the SGM, group interests do not always align (George, 2018). In particular, social profile and public acceptance of different identities among SGMs vary, with some groups more visible and/or accepted than others (Berbary & Guzman, 2018; Robinson, 2014; Waite, 2021; Winer et al, 2022; Yoshino, 1999). This quantitative study is unique in making fine distinctions among those who self‐identify with an SGM group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Issues of bisexual erasure or invisibility, both within the LGBTQIA+ community and in society broadly, have been repeatedly observed (Morgenroth et al, 2021;Pennasilico, 2019;See & Hunt, 2011;Stewart, 2021). Asexual individuals face parallel identity erasure within and beyond the queer community (Jack;Meyer, 2019;Mollet, 2021;Mollet & Lackman, 2019;Walker, 2016;Winer et al, 2022). Importantly, for future work, asexual participants noted that using LGBTQIA+ (rather than LGBT) in recruitment materials highlighted inclusion of asexual populations and encouraged participation.…”
Section: Discussionmentioning
confidence: 97%
“…The meaning of asexuality varies, and its definition is not stable (Chasin, 2011; Mitchell & Hunnicutt, 2019; Scherrer, 2008). Although asexual identity challenges the notion that everyone desires sex (Chasin, 2015; Gupta, 2015; Przybylo, 2011, 2019; Winer et al., 2022), until recently, research on asexuality has been limited. Nonetheless, various studies have found asexual men are markedly outnumbered by both women and individuals who are neither men nor women (Bogaert, 2004, 2013; Brotto et al., 2010; Greaves et al., 2017; MacNeela & Murphy, 2015; Weis et al., 2021).…”
Section: Prior Researchmentioning
confidence: 99%